Simulação de um efeito não-linear de distorção de guitarra elétrica utilizando a GPU - Guimarães, Jonathan W.; Zola, Wagner M. Nunan (Anais da Escola Regional de Alto Desempenho da Região Sul (ERAD-RS); 2020: Anais da XX Escola Regional de Alto Desempenho da Região SulDO - 10.5753/eradrs.2020.10797, 2020)
The work proposes to implement a non-linear distortion simulation model of the electric guitar signal called Waveshape, which divides this filter into three sub-filters: gain, overdrive and low-pass. We implemented the linear, monothread algorithm, executed on the CPU and distributed, multithread on the GPU, using CUDA.